Phenotype is sustained during hospital readmissions following treatment for complicated severe malnutrition among Kenyan children: A retrospective cohort study - Gonzales, GB; Ngari, MM; Njunge, JM; Thitiri, J; Mwalekwa, L; Mturi, N; Mwangome, MK; Ogwang, C; Nyaguara, A; Berkley, J (Wiley, 2019)
Hospital readmission is common among children with complicated severe acute malnutrition (cSAM) but not well-characterised. Two distinct cSAM phenotypes, marasmus and kwashiorkor, exist but their pathophysiology and whether the same phenotype persists at relapse are unclear. We aimed to test the association between cSAM phenotype at index admission and readmission following recovery. We performed secondary data analysis from a multicentre randomised trial in Kenya with one-year active follow-up. The main outcome was cSAM phenotype upon hospital readmission. Among 1704 HIV-negative children with cSAM discharged in the trial, 177 children contributed a total of 246 readmissions with cSAM. cSAM readmission was associated with age <12 months (p=0.005), but not site, sex, season nor cSAM phenotype. Of these, 42 children contributed 44 readmissions with cSAM that occurred after a monthly visit when SAM was confirmed absent (cSAM relapse). cSAM phenotype was sustained during cSAM relapse. The adjusted odds ratio for presenting with kwashiorkor during readmission after kwashiorkor at index admission was 39.3 [95% CI: 2.69 – 1326] (p = 0.01); and for presenting with marasmus during readmission after kwashiorkor at index admission was 0.02 [95% CI: 0.001 – 0.037] (p = 0.01). To validate this finding, we examined readmissions to Kilifi County Hospital, Kenya occurring at least 2 months after an admission with cSAM. Among 2412 children with cSAM discharged alive, there were 206 readmissions with cSAM. Their phenotype at readmission was significantly influenced by their phenotype at index admission(p<0.001). This is the first report describing the phenotype and rate of cSAM recurrence.